Street-based Corruption in the Philippines: Motives, Ethical Considerations and Organizational Context. (January 2014) - Nolasco, Liberty; Sevillano, Kurt; Regala, Angeli; Tieng, Deneisha
Mainstream studies generally focus on the formal organizational context of corruption, leaving out its informal complexity. This study seeks to examine street-based corruption, or kotongan, as a case of informal complexity of organizational corruption widely occurring in the major thoroughfares of the Philippines. Kotongan refers to the payment of bribe, called kotong or areglo, by the drivers to the state authorities (for example, police, traffic managers and local government personnel), respectively. This study takes the views of 16 bus and jeepney drivers based in Baclaran, Batangas, Buendia and Molino to explain the practice and enforcement of kotongan . A framework has been developed in this study in which the motives of drivers, their ethical decision-making considerations and the organizational support received by state authorities from connections serve as crucial elements. The study also reveals that corruption involves a process of communication preference for bribery, as well as the negotiation and agreement between drivers and apprehending parties. These processes are all backed up by different sets of motivators and ethical considerations in the decision making of drivers, and the changing configuration of support shown to state authorities by their connections. JEL: K42